Psychosis secondary to thyrotoxicosis: An educational review - Hana Taha; Salma Abdel Wahed; Vanja Berggren (Health Sciences Review)
Excess thyroid hormones have a major effect on brain metabolism and neurotransmitter systems. This study aimed to examine the complex relationship between thyrotoxicosis and psychosis including symptoms and treatment options. This literature review summarized 37 case reports of psychosis secondary to thyrotoxicosis that were published in PubMed, Medline, Web of Science and Google Scholar searches between Jan 2011 and Dec 2024. The results indicated that the case reports of females were significantly more than those of males. The most common psychiatric symptom was agitation (27.02 %) while mania and psychomotor agitation were the least common one (2.7 %). For thyrotoxicosis symptoms, tachycardia (32.43 %) was the most frequently mentioned symptom, and the least common ones were goiter and high blood pressure (13.51 %). The findings of this review emphasize the value of collaborative treatment combining psychiatrist and endocrinologist to address the complex clinical presentations and treatment modalities.